Pengaruh Talent Management dan Knowledge Management Terhadap Employee Retention pada Millennials Workforce yang di Moderasi oleh Employee Engagement - Nasruddin; Putri, Shara Amelia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Human Resources (HR) is a strategic element of an organization to achieve its mission, where HR plays a role as a reference point in determining policies that align with the organization's goals. The aim of this research is to determine whether talent management and knowledge management have a partial effect on employee retention in the millennial workforce and to examine whether employee engagement can moderate the relationship between talent management and knowledge management on employee retention in the millennial workforce. The sampling technique employed the Lemeshow method, resulting in a sample of 96 individuals. The study focused on a dynamic, boundaryless, digitally connected workforce that eschews conventional boundaries, namely the millennial workforce. The data used consisted of both primary and secondary data, collected through Likert scale questionnaires. Data analysis was conducted using the Multiple Regression Analysis approach. The research findings indicate that talent management does not have an impact on employee retention, while knowledge management does have an impact on employee retention. Employee engagement is found to moderate the relationship between talent management, knowledge management, and employee retention.